MODELO DE COSTEO DIRECTO – VARIABLE APLICADO EN FEALTEC DE LA CIUDAD DE LOJA, ENERO 2013 - Loja Sánchez, María José (2015)
This paper titled "Model-Direct Variable Costing applied Fealtec City Loja, January 2013" was developed as a requirement for the degree of Engineer in Accounting and Auditing, Certified Public Auditor. To develop the general objective specific objectives were established, the first thing is to determine the processes of accounting information, relevant in the administration of Fealtec, for that reference to the register of the costs for production orders is the direct cost which details each of the materials used, work orders where the control card is used to record the amount of material needed for what is sought to be used for the development of each of them, preparing work orders and complete the cost sheet where manpower was needed detailing is done, likewise the second objective is to make the application of Direct Costing. - Variable Cost as a model for decisions , for which the monthly record of costs was developed for production orders, where direct premiums Matera are determined, the registration of labor and manufacturing overhead costs, which allowed to know the total variable cost of production, plus the expenses incurred in the administration and sale of the product as they are determined: the cost of profit or loss in the development of production orders, which applies to breakeven, reflecting submits an profit or loss. The equation method that allows to know the units have been sold and finally we have the contribution margin that helped us to cover the fixed costs 5 we had in the company, and finally the state held comprehensive income where they could meet the economic and financial situation of the company. Finally the conclusions and recommendations are presented, among the most relevant is that the technical advantages of the model Direct-Variable Costing is unknown, which affects the decisions of the manager - owner, because they cannot accurately determine if there is a loss or gain at the end of the production period, the recommendations are aimed at improving the industrial service company.